A Scoping Review of Resilience-Focused Interventions of Kunjing Children in Mainland China. (March 2021) - Wang, Miao; Zhang, Qingzhu; Fan, Yao; Hong, Jun Sung
Purpose: Kunjing children refer to those who endure harsh living conditions due to family poverty, health problems, and lack of parental care in Mainland China. This scoping review aims to explore interventions promoting the resilience of kunjing children in China. Method: Both Chinese and English studies published by January 2020 were reviewed through a comprehensive search of articles in Web of Science and Chinese National Knowledge Infrastructure. Empirical studies targeting resilience-focused interventions for kunjing children in China were selected. Results: A total of 12 studies were reviewed. Seven studies tested interventions involving only kunjing children, and the other five involved both children and parents/caregivers. Children with health problems and those who lack parental care participated in the programs, but children in poverty were absent. Group-based interventions were the most commonly used programs, which were effective. Conclusion: The current state of intervention studies calls for programs that promote resilience of kunjing children and their parents/caregivers.